#TITLE_ALTERNATIVE# - ASHIF (NIM 13205052), HIFNI
Electricity market is a place where electricity transaction is performed between Genco, consumer, and ISO. Minimum requirement for electricity market is economical requirement and safety requirement. There are three types of transaction in electricity market: pool transaction, bilateral transaction, and mixed transaction. In each transaction, there are three types of cost that must be paid by Genco and consumer. First, production cost must be paid by Genco for electricity production. This cost is determined based on cost equation of each Genco and total electricity production by Genco. Second, transmission cost must be paid by Genco and consumer for using transmission network. This cost is determined based on contribution of electricity, which produced by Genco and used by consumer, in each transmission line. Third, ancillary service cost must be paid by Genco or consumer for compensation of electricity loss in line and keeping voltage quality at each bus. Consumer must pay compensation of electricity losses based on contribution of each consumer to total losses in each line. Cost for keeping voltage quality in each bus is determined by cost of addition reactive production in each bus. Power flow tracing method combined with proportional sharing principal is used for tracing origin and destination of each power that flow in each transmission line. This method is used because of its simplicity and calculation based on real power flows in each transmission line. The same method is used to determine transmission losses allocation that have to be paid by each consumer.